1966
DOI: 10.1002/1097-0142(196608)19:8<1039::aid-cncr2820190802>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid carcinoma—Biologic behavior and mortality:Postmortem findings in 42 cases, including 27 in which the disease was fatal

Abstract: Thirty‐three autopsy cases of clinical thyroid carcinoma were studied as to types, precursor changes and biologic behavior of the tumors. Eleven carcinomas were of the solid type; 13 were spindle and giant cell and the remainder were papillary, follicular or both. The findings indicate that spindle and giant cell carcinomas arise from the papillary and follicular type. No precursor changes were found in the other tumors or in 9 occult carcinomas found at autopsy. The biologic behavior of all types, other than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
3

Year Published

1974
1974
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(34 citation statements)
references
References 13 publications
0
31
0
3
Order By: Relevance
“…Six cases of scalp metastasis from MTC were reported in the literature. [5,6,[30][31][32] In five cases scalp was the only cutaneous site of metastasis and in one case chest wall was also involved. Alwaheeb et al [6] reported 2 cases of MTC presenting initially with scalp nodules.…”
Section: Medullary Carcinomamentioning
confidence: 99%
“…Six cases of scalp metastasis from MTC were reported in the literature. [5,6,[30][31][32] In five cases scalp was the only cutaneous site of metastasis and in one case chest wall was also involved. Alwaheeb et al [6] reported 2 cases of MTC presenting initially with scalp nodules.…”
Section: Medullary Carcinomamentioning
confidence: 99%
“…There is good evidence that undifferentiated carcinoma arises from papillary or follicular carcinoma (Table 1) [60,61], the latter being expected to be a more frequent precursor before iodine prophylaxis [60]. Molecular studies suggest progression from papillary cancer to a subset of undifferentiated carcinomas particularly through BRAF rather than RET mutation [62], while progression from follicular carcinoma to anaplastic carcinoma through RAS point mutation is a matter of debate [63,64].…”
Section: Undifferentiated (Anaplastic) Carcinomamentioning
confidence: 99%
“…Some authors have suggested that all ATC contain foci of WDTC and that the inability to detect these foci is due to inadequate sectioning of the specimen. [59][60][61] Papillary thyroid carcinoma is the most common type of thyroid cancer associated with ATC; biologically aggressive variants such as tall cell are more common. 62 Foci of PDTC are also common in ATC.…”
Section: Pathologymentioning
confidence: 99%